RED PALAEOSOLS SEQUENCE IN A SEMIARID MEDITERRANEAN ENVIRONMENT REGION - González Martín J.A.; Rubio Fernández V.; García Giménez R.; Jiménez Ballesta R. (My University, 2007)
In this work we study one of the most palaeopedological sequence formed in Central Spain, which is located on the Pliocene–Pleistocene erosional surface in the Madrid Basin. We also analyse its relationship to erosive and sedimentary Pleistocene events in order to obtain new data for a correct interpretation of the origin and evolution of forms at the top of tabular lands in this site. The geomorphic features and the properties of a sequence of very red palaeosols that developed on this old surface can help us in the understanding of the palaeoclimatic evolution of Central Spain in a Mediterranean climate. They were examined to identify pedologic and climatic changes during the Quaternary. The soil sequence comprises intercalated palaeoargillic and palaeopetrocalcic horizons. The clay minerals are mainly illite, kaolinite, smectite and sepiolite. The alternation of argillic and calcic horizons, limestone debris (cryoclastic colluvions) and aeolian sands suggests succeeding periods of phytostability and phytoinstability (biostasis/rhexistasis). Argillation, rubification and calcium carbonate accumulation were repeated throughout the Pleistocene and it is hypothesised that climatic conditions during numerous stages of this period were not very different from the present conditions.
Keywords: PALAEOSOLS; PALAEOCLIMATE; PLEISTOCENE; MEDITERRANEAN; RED SOILS; CENTRAL SPAIN; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен